2014
DOI: 10.1111/gcb.12574
|View full text |Cite
|
Sign up to set email alerts
|

Climate extremes drive changes in functional community structure

Abstract: The response of communities to climate extremes can be quite variable. Much of this variation has been attributed to differences in community-specific functional trait diversity, as well as community composition. Yet, few if any studies have explicitly tested the response of the functional trait structure of communities following climate extremes (CEs). Recently in South Florida, two independent, but sequential potential CEs took place, a 2010 cold front, followed by a 2011 drought, both of which had profound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
105
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(109 citation statements)
references
References 52 publications
4
105
0
Order By: Relevance
“…One of the most prevalent mechanisms to explain boom-and-bust cycles of native fishes is the effect of the interaction of environmental factors and life history traits on annual recruitment (e.g., Lobon-Cervia 2009, Matthews and MarshMatthews 2011). This is likely a rich area of future research investigating population fluctuations of Florida non-natives (e.g., the influence of major cold events; Schofield et al 2010, Harrison et al 2013, Boucek and Rehage 2014. As suggested by the present study, biotic resistance through predation likewise may prove an important mechanism.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…One of the most prevalent mechanisms to explain boom-and-bust cycles of native fishes is the effect of the interaction of environmental factors and life history traits on annual recruitment (e.g., Lobon-Cervia 2009, Matthews and MarshMatthews 2011). This is likely a rich area of future research investigating population fluctuations of Florida non-natives (e.g., the influence of major cold events; Schofield et al 2010, Harrison et al 2013, Boucek and Rehage 2014. As suggested by the present study, biotic resistance through predation likewise may prove an important mechanism.…”
Section: Discussionmentioning
confidence: 58%
“…Predation by native species is seldom thought to be the cause of these newer examples (but see Sheehy and Lawton 2014). Boom-and-bust cycles and spontaneous population collapse for non-native fishes in Florida are mentioned in the literature but accounts are largely anecdotal (but see Harrison et al 2013 andBoucek and for cold effects). Although cichlids are among the most numerous and successful established non-native fishes in Florida (Shafland et al 2008), population abundance and range of several species have fluctuated considerably and some species have disappeared from the state, generally with no known cause (Shafland 1996, Shafland et al 2008, USGS 2015.…”
Section: Discussionmentioning
confidence: 99%
“…A major breakthrough in community ecology studies has been the incorporation of functional approaches and functional diversity measures, as an elucidating tool to explore species coexistence and impacts on ecosystem functioning (Mouillot et al, 2007(Mouillot et al, , 2013Boucek and Rehage, 2014). Functional diversity refers to the functional component of biodiversity and is usually measured by species traits (Violle et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Spiller et al (2010) found that the abundance of terrestrial predators increased with marine subsidies on islands, while Boucek and Rehage (2014) found that disturbance from two extreme climate events greatly altered fish community composition. However, there is a unique and well-known example in nature where a substantial resource pulse and disturbance occur simultaneously.…”
Section: Introductionmentioning
confidence: 99%